Strategi Pemilihan Transporter dan Jenis Truk Menggunakan Linear Programming Model - Djamaris, Aurino RA; Priyanto, Adi Budi (Business and Management Review, 2011)
Paying system for delivery depends on delivery area and type of truck. All transporters have different rental cost. Best selection of transporter and type of truck can achieve the minimum point of transportation cost. To get this minimum transportation cost, this research attempts to use linear programming. Linear programming model is decision making tools to maximize or minimize the function. Delivery process need information, such as route plan, transporter, and the type of truck will be used. Route plan will be planned per day when trucks want to deliver to one area and no different area combination. This research will use linear programming model to analyze transporter and type of truck selection. This research will develop three alternatives. These three alternatives will be compared to the real condition of the cost and the number of truck to get the minimum transportation cost for PT XYZ. Keywords: Transportation Cost, Transporter, Type of Truck, Route Plan, Linear Programming Model.